Data, models, and decisions : the fundamentals of management science - Bertsimas, Dimitris; Freund, Robert Michael (Belmont, Massachusetts : Dynamic Ideas, 2004)
Combines topics from two traditionally distinct quantitative subjects, probability/statistics and management science/optimization, in a unified treatment of quantitative methods and models for management. Stresses those fundamental concepts that are most important for the practical analysis of management decisions: modeling and evaluating uncertainty explicitly, understanding the dynamic nature of decision-making, using historical data and limited information effectively, simulating complex systems, and allocating scarce resources optimally.
Decision analysis -- Fundamental of discrete probability -- Continuous probability distributions and their applications -- Statistical sampling -- Simulation modeling : concepts and practice -- Regression models : concepts and practice -- Linear optimization -- Nonlinear optimization -- Discrete optimization -- Integration in the art of decision modeling.
Committed to retain
Includes bibliographical references and index.
Keywords: Management science; Decision making; Decision making; Management science